2009
DOI: 10.1111/j.1574-6968.2008.01463.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of MRSA biofilms to denture-cleansing agents

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is an important nosocomial pathogen, which is responsible for considerable morbidity and mortality in the United Kingdom. The major reservoir of this organism is thought to be the anterior nares, but there is increasing evidence that this pathogen is present in the oral cavity, particularly in denture wearers. The purpose of this study was to determine whether MRSA, grown as biofilms on denture acrylic resin, could be eradicated using commercially available ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
7

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 18 publications
1
23
0
7
Order By: Relevance
“…42 Other studies have not identified reduced susceptibility for all biocides or organisms tested. 20,24,43,44 It is difficult to determine the relative importance of organism, biocide and testing conditions in these studies that found little or no reduced biocide susceptibility associated with biofilms.…”
Section: Biocide Susceptibilitymentioning
confidence: 98%
See 1 more Smart Citation
“…42 Other studies have not identified reduced susceptibility for all biocides or organisms tested. 20,24,43,44 It is difficult to determine the relative importance of organism, biocide and testing conditions in these studies that found little or no reduced biocide susceptibility associated with biofilms.…”
Section: Biocide Susceptibilitymentioning
confidence: 98%
“…One important factor is the maturation of the microbes tested, which ranges from cells attached to surfaces for hours to samples extracted from continuously fed biofilm reactors that are weeks old. 24,25 Furthermore, few studies have controlled for cell density in attached cells or biofilms compared with planktonic culture. 26 Thus, although several studies have suggested that cell density alone does not explain the reduced susceptibility of biofilms to biocides, it is difficult to be certain of the impact of the biofilm phenotype independent of cell density in many studies.…”
Section: Biocide Susceptibilitymentioning
confidence: 99%
“…A microaerophilic atmosphere was achieved using a gas mixture (2% O 2 , 3% CO 2 , 95% N 2 at 200 × 10 5 Pa) pumped into the chamber through a filtered inlet at a rate of 200 cm 3 /min. Duplicate disks were removed from the CDFF at 48 h (early biofilms) and 168 h (established biofilms) [11] post-delivery of the second inoculum, were dipped briefly into sterile phosphate-buffered saline (PBS) (Oxoid Ltd.) to remove any planktonic organisms and were exposed to 0.2% w/v delmopinol hydrochloride solution (Decapinol ® ; Sinclair Pharmaceuticals Ltd., Godalming, UK), 0.2% and 2% w/v chlorhexidine (Sigma-Aldrich, Poole, UK) and PBS (Oxoid Ltd.) for time intervals of 5, 10 and 20 min.…”
Section: Exposure Of Multispecies Biofilmsmentioning
confidence: 99%
“…In some instances where an individual has decreased motor coordination or is disabled, chemical cleansers are necessary adjuncts to mechanical cleansing 20,21) as they are easy to use and may reach undercuts otherwise left unclean. Several studies have demonstrated the efficacy of denture cleansers to reduce biofilm formation, making them a necessary adjunct in removable prostheses hygiene 9,[22][23][24][25] . While denture cleansing agents can be important for maintaining denture hygiene and preventing colonization, they can have deleterious effects on the physical and mechanical properties of PMMA 26,27) , especially leading to an increase in surface roughness 28) .…”
Section: Introductionmentioning
confidence: 99%
“…Denture biofilms can easily form, aided by the porous acrylic surface, are quite complex 2) , and have been associated with oral infections such as denture-induced stomatitis [3][4][5][6][7] . Candida species are dominant in these biofilms, but another pathogen, methicillin-resistant Staphylococcus aureus (MRSA) has also been isolated from the oral cavity and removable dentures of elderly or hospitalized patients [8][9][10] . The presence of MRSA is of growing concern as it could have implications in regard to cross infection and involvement in systemic infection 8,11,12) .…”
Section: Introductionmentioning
confidence: 99%